Model Knowledge management di Perpustakaan Universitas Informatika dan Bisnis Indonesia (UNIBI) - Annisya Nailah Balqis; Mugi Puspita (LPPM UNIBI, 2023)
Knowledge management in the university library will encourage knowledge collection and knowledge dissemination, promote the scientific work of the academic community, and protect intellectual property. The application of knowledge management in higher education libraries aims to store tacit and explicit knowledge so that if needed again by individuals or organizations it can be utilized. The college library is an important for storing all academic knowledge and literature related to the fields of study taught in universities. The purpose of this research is to have a knowledge management proposed model in the library of the University of Informatics and Business Indonesian. The research was conducted using SWOT analysis to obtain the Knowledge management model in the library of the University of Informatics and Business Indonesian. The results obtained from the proposed model of the Knowledge management process at the Library of Informatics and Business Indonesia, namely knowledge creation, knowledge acquisition, knowledge storage, knowledge sharing, and knowledge application.